ASSESSING THE SATISFACTION WITH THE SERVICE QUALITY OF STUDENTS IN THE FACULTY OF ACCOUNTING AND BUSINESS MANAGEMENT ATVIETNAM NATIONAL UNIVERSITY OF AGRICULTURE - Nga, Bui; Anh, Nguyen (Tạp chí Khoa học Nông nghiệp Việt Nam, 2024)
With the increasing numbers of higher education institutions, universities in general, and Vietnam National University of Agriculture (VNUA) in particular, are trying to attract more students by offering all possible efficient services and providing highest satisfaction. This paper aimed at measuring the satisfaction of the students at the Faculty of Accounting and Business Management (FABM) at VNUA with the quality of university services. Questionnaires were used to collect data from 102 current students in FABM. The results showed that the quality of the main groups of services at VNUA is evaluated from moderate to good levels. A half of interviewed students were satisfied with services at the average satisfaction index of 3.36. The availability of the current service is sufficient to meet the needs of the students in the major of Accounting and those of first and second year students while this was not be satisfied for the students majoring in Business Management and the senior students. The research provides some suggestions to improve the students’ satisfaction by investing in infrastructure and facilities, improving the internal internet network, and enhancing professional qualification for administrative staff.